Harvest of Souls: the Jesuit Missions and Colonialism in North America, 1632-1650 - Blackburn, Carole (McGill-Queen's University Press, 2000)
"In Harvest of Souls Carole Blackburn uses the Jesuit Relations to shed light on the dialogue between Jesuit missionaries and the Native peoples of northeastern North America, providing a historical anthropology of two cultures attempting to understand, contend with, and accommodate each other in the new world." "Harvest of Souls is essential for all those interested in new approaches to historical and contemporary relations between Europeans and Native people in North America."--Jacket.
Keywords: Communautés religieuses; Jésuites

Catalogue des imprimés des XVe et XVIe siècles dans les collections de l'Université du Québec à Montréal - Dunn-Lardeau, Brenda (Presses de l'Université du Québec, 2013)
Keywords: Communautés religieuses; Jésuites

Paul Lejeune (1591-1664), missionnaire de Nouvelle-France, le premier linguiste et grammairien de l'innu - Laflèche, Guy (Les Éditions du Singulier, 2017)
Keywords: Autochtones; Communautés religieuses; Jésuites; Langue